Preparation of Cetane Improver for Diesel Fuel and Study It’s Performance - Khudhair, Muna Mahmood; Husain, Sajeda Abbas; Salih, Shafaa Mahdi; Jassim, Zahraa Mahmed (Al-Nahrain Journal of Science, 2017)
Cetane improver is an additive that improves the cetane number of diesel fuel. Now the world focus on using cetane improvers which are friend to environmental that biodegradable and reduce exhaust of gases such as carbon monoxide and oxide of nitrogen. Cetane improver was prepared by reacting methyl ethyl ester of long chain fatty acids with nitric acid in the presence of acetic anhydride in nitration process, while the ester can be produced from castor oil through transesterification. In this work the optimum conditions of nitration reaction which includes mole ratio of nitric acid, temperature and time of reaction were studied according to the results of percent of yield and absorbance peak area of OH group of starting materials. It was found that 10 is best mole ratio of nitric acid to esters, 10-20˚c temperature for 3hours time. The nitrated products were analyzed as cetane number enhancers adding it to diesel fuel at 0.1 and 0.05% concentration and it was found that the cetane number of diesel fuel was increased at 25% percentage.